Nueva Ecija’s Philippine Lime (Citrofortunella microcarpa) Agribusiness Industry: Marketing Disputes and Economic Outlooks - Quijano, Ma Florisa; Quijano, Gerald; Diaz, Rowell (Asian Journal of Agriculture and Rural Development, 2022)
Philippine lime or calamansi is considered one of the Philippine high-value crops in Nueva Ecija province. This article presents some issues and problems of the calamansi industry in terms of marketing. The study used a descriptive survey of 56 farm-owners or calamansi growers. Findings revealed that lime production could be a stable income source if the growers could provide the necessary production inputs on a sustainable basis. Calamansi farmers in the province are often confronted with the following problems: the high cost of farm inputs, price fluctuations, price manipulation of big-time traders, and other intermediaries. The study also found that the existing actors in the chain were limited to growers, laborers, agri-supply shops, nursery owners, intermediaries, and traders. In terms of trading, there is a high degree of competition among traders in the market. The findings and results from this study may be important factors in developing and designing effective agricultural marketing program and startegic development plan by the authorities in the region.